An Analysis of Pivot Grammar Used by Pupils in Playgroup At-Taqwa Surabaya - Mery Claudia Laayranita; Wijayadi -; Linda Mayasari (Tell : Teaching of English Language and Literature Journal, 2015)
This article entitled An Analysis Of Pivot Grammar Used By Pupils In Playgroup Attaqwa Surabaya. Language is the most important mean of communication in every human being. Language is obtained since human were in mother’s womb. Therefore, the researcher analyzes the pupils production of the utterance at the age of two to three years old in at-taqwa playgroup, meaning and description about pupils utterances. The design of researcher is descriptive qualitative research. It contains the description of pupil’s utterance in at-taqwa playgroup. The result of the study shows that in many activities of observation most pupils in at-taqwa playgroup use two utterances that are referred as pivot grammar.